Evaluation of serum B7‐H3 expression, ultrasound and clinical characteristics to predict the risk of cervical lymph node metastases in papillary thyroid carcinoma by nomogram. Issue 1 (16th December 2022) - Huang, Yingcheng; Huang, Zehao; Cai, Huizhu; Zhuge, Lingdun; Wang, Shixu; Yan, Dangui; Zhang, Xiwei; An, Changming; Niu, Lijuan; Li, Zhengjiang
Abstract: Background: Improving the preoperative diagnosis of cervical lymph node metastasis (LNM) will help improve the clinical outcomes of papillary thyroid carcinoma (PTC) patients. B7‐H3, as an immune checkpoint of the B7 family, is highly expressed in PTC tissues and related to LNM and prognosis. We aimed to explore the clinical values of serum B7‐H3 (sB7‐H3) in predicting LNM in PTC by a nomogram prediction model. Methods: From September 2019 to May 2021, a total of 344 PTC patients with primary surgery in our hospital were enrolled in this research. Enzyme‐linked Immunosorbent Assay (ELISA) was used to detect sB7‐H3 from the peripheral blood of PTC patients and normal controls. We created a nomogram prediction model in combination with sB7‐H3 expression, clinical and ultrasound characteristics to predict LNM in the early stage. Results: Gender ( p = 0.001), age ( p = 0.015), tumor size ( p < 0.001), number of tumors ( p = 0.021) and sB7‐H3 expression ( p = 0.003) were independent risk factors for LNM in PTC. All the factors were included in the nomogram. The area under the curve (AUC) was 73.9% (95% CI, 68.12%–79.69%). Conclusion: The nomogram is helpful in assessing the risk of LNM in PTC. sB7‐H3 has excellent potential in predicting LNM in patients with PTC as an adjunctive ultrasound tool. Abstract : In this study, we detected and compared the serum B7‐H3 expression in papillary thyroid carcinoma (PTC) and normal controls. Meantime, a nomogram prediction model in combination with sB7‐H3 expression, clinical and ultrasound characteristics were created to predict LNM in early stage. We found that sB7‐H3 has great potential in predicting LNM in patients with PTC as an adjunctive tool of ultrasound.